2012
DOI: 10.1093/schbul/sbs123
|View full text |Cite
|
Sign up to set email alerts
|

Stable Cognitive Deficits in Schizophrenia Patients With Comorbid Obsessive-Compulsive Symptoms: A 12-Month Longitudinal Study

Abstract: OCSs in schizophrenia is associated with specific and longitudinally stable cognitive deficits, strongly arguing for at least partially overlapping neurobiological mechanisms with OCD. Prospective studies involving patients with at-risk mental states for psychosis are necessary to decipher the interaction of cognitive impairment and the clinical manifestations of schizophrenia and OCSs. This might facilitate the definition of patients at high risk for OCSs, an early detection of subclinical levels, therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 37 publications
3
42
0
5
Order By: Relevance
“…Similar associations have previously been reported [49][50][51][52] and seem to be mainly independent of SGA treatment. 53 Consequently, some authors have proposed deficits in these domains as cognitive endophenotyps of OCS in patients with schizophrenia. 54 …”
Section: Association Between Ofc Activation Cognitive Deficits and Ocsmentioning
confidence: 99%
“…Similar associations have previously been reported [49][50][51][52] and seem to be mainly independent of SGA treatment. 53 Consequently, some authors have proposed deficits in these domains as cognitive endophenotyps of OCS in patients with schizophrenia. 54 …”
Section: Association Between Ofc Activation Cognitive Deficits and Ocsmentioning
confidence: 99%
“…In addition, they present with specific neurocognitive deficits (Schirmbeck et al, 2012b), more often utilize health care services (Berman et al, 1995a), and show heightened levels of anxiety and depression (Lysaker and Whitney, 2009) when compared to schizophrenia patients without OCS. These pronounced impairments result in an additional burden of disease, in poorer social and vocational function (Fenton and McGlashan, 1986; Lysaker et al, 2004; Öngür and Goff, 2005; de Haan et al, 2013) and in a less favorable overall prognosis (Schirmbeck and Zink, 2013).…”
Section: Epidemiology Of Ocs In Schizophreniamentioning
confidence: 99%
“…One large investigation from the Netherlands followed participants over a period of 5 years and described a predominantly fluctuating course of OCS severity in over 70% of the comorbid sample: Some patients experienced the remission of OCS, others a fluctuating, more or less cyclic course, some reported first onset of OCS, whereas a forth group showed persisting symptom severity (Mahasuar et al, 2011). Another longitudinal study in a German sample investigated two pharmacological diverse groups and found persisting OCS severity over 12 months in the group treated with clozapine (CLZ) and olanzapine (OLZ) (Schirmbeck et al, 2012b, 2013). The diverse clinical course adds to the heterogeneous clinical presentation and suggests an involvement of different environmental factors and/or symptom interactions in the longitudinal development of comorbid OCS in schizophrenia (see section Underlying neurobiological mechanisms and environmental factors).…”
Section: Clinical Presentation and Explanatory Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of OCS in schizophrenia seems to be associated with poor outcomes such as earlier age of onset (Faragian et al, 2012), poorer treatment response (Zink et al, 2014), more depressive (de Haan et al, 2013) and negative symptoms (Owashi et al, 2010) and greater cognitive deficits (Patel et al, 2010;Schirmbeck et al, 2013b). It remains unknown whether treatment for the OCS reverts these outcomes.…”
Section: Introductionmentioning
confidence: 99%